Pedagogical Gaps and Language Barriers: The Relationship Between Teaching Methods and English Learning Difficulties - Muhammad Surya Rifqi; Armin Fani (Explorations in English Learning, 2025)
Language learning success in English as a Foreign Language (EFL) contexts is strongly influenced by instructional practices employed in the classroom. This study aimed to investigate the relationship between teaching methods and students’ English learning difficulties at SMKN 4 Banjarmasin, focusing on areas such as pronunciation, grammar, vocabulary, and comprehension. A quantitative correlational research design was employed. The population consisted of 90 second-grade students, from which 20 students were selected through purposive sampling. Data were collected using a structured questionnaire adapted from previous research and a classroom observation checklist. The questionnaire demonstrated good reliability, with a Cronbach’s Alpha coefficient of 0.82. Descriptive statistics were used to summarize students’ perceptions, while Pearson Product Moment correlation was applied to examine the relationship between variables. The findings revealed that students experienced the greatest difficulties in pronunciation and grammar, while vocabulary posed fewer challenges. Classroom observations indicated that limited instructional variation, inconsistent use of learning media, and insufficient adaptation to students’ proficiency levels contributed to these difficulties. The correlation analysis showed a significant negative relationship between teaching methods and learning difficulties (r = −0.68, p < .01), indicating that improved instructional quality is associated with reduced learning difficulties. These results suggest that clear explanations, varied teaching strategies, interactive activities, and targeted feedback can positively influence students’ English learning outcomes. The study concludes that enhancing teaching methods is essential for reducing learning difficulties and improving English instruction in vocational high school EFL contexts.